Factors associated with repeated outbreak of anthrax in Bangladesh: qualitative and quantitative study - Hassan, jayedul; Ahsan, Md. Murshidul; Rahman, Md. Bahanur; Chowdhury, Shah Md. Ziqrul Haq; Parvej, Md. Shafiullah; Nazir, KHM Nazmul Hussain (Journal of Advanced Veterinary and Animal Research, 2015)
Anthrax, caused by Bacillus anthracis is an acute, febrile disease of warm blooded animals including humans. Social norms and poverty in addition to climatic factors such as soil conditions, seasons of year, ambient temperature and rainfall influence the persistence of the B. anthracis and anthrax outbreaks. The present study was designed to reveal the factors influencing the repeated outbreak of anthrax in Bangladesh. Considering the previous outbreaks of anthrax, Sirajganj, Bogra, Kushtia, Tangail and Mymensingh districts of Bangladesh were selected for this study. To elucidate the factors, qualitative data relating to the animal management, knowledge and behavior of the people; and quantitative data relating to soil conditions, ambient temperature and rainfall were acquired, and analyzed critically. Based on the outbreak histories, a year was divided into two seasons, anthrax prone season (May-November) and anthrax dry season (December-April). Anthrax spores could be isolated from 11.67% (n=14/120) of the soil samples collected from the study areas. The present study revealed that poor knowledge, lack of awareness, improper carcass disposal, inadequate vaccination, high Ca content and moisture in the soil along with high ambient temperature and rainfall during the anthrax prone season were the possible influencing factors of repeated outbreaks of anthrax in the study areas. Intensive propaganda to create public awareness of anthrax together with proper vaccination may reduce anthrax outbreaks in Bangladesh. http://dx.doi.org/10.5455/javar.2015.b72